Whole-genome sequencing analysis of multidrug-resistant Serratia marcescens isolates in an intensive care unit in Brazil - Thalita PPS Cruz; Francisco KSF Azevedo; Marco A Pepato; Paula S Rizzo; Francisco JD Souto; Bertram Brenig; Aristóteles Góes-Neto; Siomar C Soares; Rommel TJ Ramos; Vasco AC Azevedo; Mateus M Costa; Leonardo Broetto; et al. (Journal of Infection in Developing Countries)
Introduction: Serratia marcescens is an opportunistic pathogen found ubiquitously in the environment and associated with a wide range of nosocomial infections. This multidrug-resistant bacterium has been a cause of concern for hospitals and healthcare facilities due to its ability to spread rapidly and cause outbreaks. Next generation sequencing genotyping of bacterial isolates has proven to be a valuable tool for tracking the spread and transmission of nosocomial infections. This has allowed for the identification of outbreaks and transmission chains, as well as determining whether cases are due to endogenous or exogenous sources. Evidence of nosocomial transmission has been gathered through genotyping methods. The aim of this study was to investigate the genetic diversity of carbapenemase-producing S. marcescens in an outbreak at a public hospital in Cuiaba, MT, Brazil.